Retinal Neuronal Loss in Visually Asymptomatic Patients With Myoclonic Epilepsy With Ragged-Red Fibers. Issue 1 (March 2019) - Najjar, Raymond P.; Reynier, Pascal; Caignard, Angélique; Procaccio, Vincent; Amati-Bonneau, Patrizia; Mack, Heather; Milea, Dan
Abstract : Background: Myoclonic epilepsy with ragged-red fibers (MERRF, OMIM, #545000) is a rare neurological condition mostly caused by the m.8344A>G mitochondrial DNA pathogenic variant, which can variably affect multiple tissues, including the retina and optic nerve. We report detection of visually asymptomatic neuroretinal loss in 3 patients with genetically confirmed MERRF, using spectral domain optical coherence tomography (SD-OCT). Methods: All patients underwent a complete ophthalmic examination including assessments of visual acuity, color vision, pupillary reactions, extraocular movements, applanation tonometry, slit-lamp, and dilated fundus examinations. Standard automated perimetry or Goldmann kinetic perimetry was performed, as well as fundus photographs and SD-OCT of the optic nerve head and macula. Results: Despite the absence of visual symptoms in all patients, and normal visual acuity and visual fields in 1 patient, the 3 genetically confirmed patients (point mutations m.8344A>G; age range: 18–62 years) with MERRF-related neurological manifestations, displayed thinning of the retinal nerve fiber layer and variable alterations of the macular ganglion cell complex. Conclusions: Visually asymptomatic patients with genetically confirmed MERRF can display features of structural neuroretinal loss, quantifiable with SD-OCT. Further investigations are needed to establish whether OCT can assess early neurodegeneration in MERRF.